e-Modyul: Technical-vocational-livelihood support learning management system - Quimod, Marco T; Alegata, Wayne Custer G; Madrigal, Dennis V (Technium Education and Humanities, 2023)
e-MODYUL: Technical-Vocational-Livelihood Support Learning Management System is a mobile and web-based application running on Android and IOS platforms and other operating systems. This application would serve as an aid to help the students in accessing their lessons and answering their tests and examinations regardless of the type of operating system that they are going to use. Students can also use the application using different types of computers. Upon using the application, students will enjoy learning and accessing resources of the application at their own pace. e-MODYUL TVL application is designed for students to help them understand their lessons with the same objectives and for schools to achieve their goals of providing quality education using a blended type of learning. This application will help teachers and students find the balance in delivering learning to every Filipino learner. Using paper and pen and financial problems in going to school are just some of the problems encountered by the students. Watching relevant tutorial videos related to TVL are also needed. Based on these problems and challenges presented, the proponent develops this e-MODYUL Technical-Vocational-Livelihood Support Learning Management System with these features; a progress tracking system, interactive, user-friendliness, secured, and cross-platform dynamic environment. The e-MODYUL mobile app has six functions, namely, sign-in / out, log-in/out, TVL learning resources, assessments, settings, and progress tracking. Users, both the students and the teachers, can Log-in and Log-out of the system by using their credentials. PHP Hypertext Preprocessor language was used to develop the application and to break down modules in this application. The rapid application development (RAD) model was used in this capstone project up to the completion of the final product. Different stages were needed as a primary requirement for user description and planning. Users were provided with sample screen images for the application for them to familiarize the different interfaces, whether web-based or mobile. These interfaces were designed to be responsive regardless of any platform. All interfaces were user-friendly and easy to use and navigate. Respondents described the mobile learning resource application as an excellent innovation since all of the attributes are said to be "Excellent". Attributes described are accuracy, user-friendly, operability, consistency, conciseness, compatibility, and simplicity. Thirty respondents were selected to test the application, whereas 10 were teachers and 20 were students. After the data were gathered, the proponent used frequency distribution to determine if the purpose of the mobile learning resource app had been achieved. Then the average results were generated, and the percentile rank and mean scores were computed. The development of the application helps students and teachers provide quality education while using technology, particularly paperless technology. It was revealed in this research that we could innovate education with the aid of application. The application can be more accessible if uploaded to Google Play Store, where everyone can download it.